2022
DOI: 10.48550/arxiv.2202.02275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inverse-Compton Scattering of the Cosmic Infrared Background

Alina Sabyr,
J. Colin Hill,
Boris Bolliet

Abstract: The thermal Sunyaev-Zel'dovich (tSZ) effect is the distortion generated in the cosmic microwave background (CMB) spectrum by the inverse-Compton scattering of CMB photons off free, energetic electrons, primarily located in the intracluster medium (ICM). Cosmic infrared background (CIB) photons from thermal dust emission in star-forming galaxies are expected to undergo the same process. In this work, we perform the first calculation of the resulting tSZ-like distortion in the CIB. Focusing on the CIB monopole, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…It was also shown that the scattering of the CIB by clusters can in principle be used to study the evolution of this background [49,50]. The expressions given here can be used to improve the modeling including non-thermal effects and anisotropies in the distribution functions.…”
Section: Applications Beyond the Sz Effectmentioning
confidence: 98%
“…It was also shown that the scattering of the CIB by clusters can in principle be used to study the evolution of this background [49,50]. The expressions given here can be used to improve the modeling including non-thermal effects and anisotropies in the distribution functions.…”
Section: Applications Beyond the Sz Effectmentioning
confidence: 98%